INCOME CONTRIBUTION OF WOMEN DUCK FARMERS TO FAMILY INCOME IN BATE PUTEH VILLAGE, LANGSA LAMA SUBDISTRICT, LANGSA CITY, ACEH - Fitri, Rahmatul; Basriwijaya, Kiagus M. Zain; Anzhita, Silvia (Syarif Hidayatullah State Islamic University Jakarta, 2024)
This study aims to analyze the income contribution and working time allocation of women duck farmers in Batee Puteh Village, Langsa Lama Subdistrict, Langsa City, Aceh, in supporting family income. The sampling technique used was a census or Saturated Sampling method, with a sample size of 12 women duck farmers. The data analysis methods employed are income analysis and the Harvard analysis method. The study results show that the average total working hours of women farmers across all activities is 11.66 hours per day, or 48.58%, with a rest time of 12.33 hours per day. The net income received by women meat duck farmers is IDR 6,003,908 per year, while women laying duck farmers earn IDR 1,972,013 per year. Consequently, the average total net income received by women duck farmers is IDR 3,987,960 per month. Women duck farmers contribute 13.08% to the family income. Hypothesis testing was conducted to determine the income contribution of women duck farmers in enhancing family income. The income contribution of women duck farmers, at 17.48%, falls into the low category. Activities were divided into production, predominantly managed by women; reproductive tasks, also predominantly managed by women; and social and community activities, which were shared by both genders.